At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Let's solve each subtraction problem by rewriting it into an addition problem where we add the opposite.
#### Problem 8:
[tex]\[ 14 - 6 \][/tex]
Rewrite this as:
[tex]\[ 14 + (-6) \][/tex]
Calculating this, we get:
[tex]\[ 14 + (-6) = 8 \][/tex]
So,
[tex]\[ 14 - 6 = 8 \][/tex]
#### Problem 13:
[tex]\[ 2 - (-3) \][/tex]
Rewrite this as:
[tex]\[ 2 + 3 \][/tex]
Calculating this, we get:
[tex]\[ 2 + 3 = 5 \][/tex]
So,
[tex]\[ 2 - (-3) = 5 \][/tex]
#### Problem 14:
[tex]\[ -3 - 2 \][/tex]
Rewrite this as:
[tex]\[ -3 + (-2) \][/tex]
Calculating this, we get:
[tex]\[ -3 + (-2) = -5 \][/tex]
So,
[tex]\[ -3 - 2 = -5 \][/tex]
#### Problem 15:
[tex]\[ -4 - (-5) \][/tex]
Rewrite this as:
[tex]\[ -4 + 5 \][/tex]
Calculating this, we get:
[tex]\[ -4 + 5 = 1 \][/tex]
So,
[tex]\[ -4 - (-5) = 1 \][/tex]
#### Problem 16:
[tex]\[ 2 - 5 \][/tex]
Rewrite this as:
[tex]\[ 2 + (-5) \][/tex]
Calculating this, we get:
[tex]\[ 2 + (-5) = -3 \][/tex]
So,
[tex]\[ 2 - 5 = -3 \][/tex]
#### Problem 17:
[tex]\[ 3 - (-3) \][/tex]
Rewrite this as:
[tex]\[ 3 + 3 \][/tex]
Calculating this, we get:
[tex]\[ 3 + 3 = 6 \][/tex]
So,
[tex]\[ 3 - (-3) = 6 \][/tex]
#### Problem 18:
[tex]\[ 4 - (-3) \][/tex]
Rewrite this as:
[tex]\[ 4 + 3 \][/tex]
Calculating this, we get:
[tex]\[ 4 + 3 = 7 \][/tex]
So,
[tex]\[ 4 - (-3) = 7 \][/tex]
#### Problem 19:
[tex]\[ -7 - (-2) \][/tex]
Rewrite this as:
[tex]\[ -7 + 2 \][/tex]
Calculating this, we get:
[tex]\[ -7 + 2 = -5 \][/tex]
So,
[tex]\[ -7 - (-2) = -5 \][/tex]
#### Problem 20:
[tex]\[ -9 - 1 \][/tex]
Rewrite this as:
[tex]\[ -9 + (-1) \][/tex]
Calculating this, we get:
[tex]\[ -9 + (-1) = -10 \][/tex]
So,
[tex]\[ -9 - 1 = -10 \][/tex]
#### Problem 21:
[tex]\[ 0 - (-9) \][/tex]
Rewrite this as:
[tex]\[ 0 + 9 \][/tex]
Calculating this, we get:
[tex]\[ 0 + 9 = 9 \][/tex]
So,
[tex]\[ 0 - (-9) = 9 \][/tex]
Summarizing all our results:
1. [tex]\( 14 - 6 = 8 \)[/tex]
2. [tex]\( 2 - (-3) = 5 \)[/tex]
3. [tex]\( -3 - 2 = -5 \)[/tex]
4. [tex]\( -4 - (-5) = 1 \)[/tex]
5. [tex]\( 2 - 5 = -3 \)[/tex]
6. [tex]\( 3 - (-3) = 6 \)[/tex]
7. [tex]\( 4 - (-3) = 7 \)[/tex]
8. [tex]\( -7 - (-2) = -5 \)[/tex]
9. [tex]\( -9 - 1 = -10 \)[/tex]
10. [tex]\( 0 - (-9) = 9 \)[/tex]
These are your solutions!
#### Problem 8:
[tex]\[ 14 - 6 \][/tex]
Rewrite this as:
[tex]\[ 14 + (-6) \][/tex]
Calculating this, we get:
[tex]\[ 14 + (-6) = 8 \][/tex]
So,
[tex]\[ 14 - 6 = 8 \][/tex]
#### Problem 13:
[tex]\[ 2 - (-3) \][/tex]
Rewrite this as:
[tex]\[ 2 + 3 \][/tex]
Calculating this, we get:
[tex]\[ 2 + 3 = 5 \][/tex]
So,
[tex]\[ 2 - (-3) = 5 \][/tex]
#### Problem 14:
[tex]\[ -3 - 2 \][/tex]
Rewrite this as:
[tex]\[ -3 + (-2) \][/tex]
Calculating this, we get:
[tex]\[ -3 + (-2) = -5 \][/tex]
So,
[tex]\[ -3 - 2 = -5 \][/tex]
#### Problem 15:
[tex]\[ -4 - (-5) \][/tex]
Rewrite this as:
[tex]\[ -4 + 5 \][/tex]
Calculating this, we get:
[tex]\[ -4 + 5 = 1 \][/tex]
So,
[tex]\[ -4 - (-5) = 1 \][/tex]
#### Problem 16:
[tex]\[ 2 - 5 \][/tex]
Rewrite this as:
[tex]\[ 2 + (-5) \][/tex]
Calculating this, we get:
[tex]\[ 2 + (-5) = -3 \][/tex]
So,
[tex]\[ 2 - 5 = -3 \][/tex]
#### Problem 17:
[tex]\[ 3 - (-3) \][/tex]
Rewrite this as:
[tex]\[ 3 + 3 \][/tex]
Calculating this, we get:
[tex]\[ 3 + 3 = 6 \][/tex]
So,
[tex]\[ 3 - (-3) = 6 \][/tex]
#### Problem 18:
[tex]\[ 4 - (-3) \][/tex]
Rewrite this as:
[tex]\[ 4 + 3 \][/tex]
Calculating this, we get:
[tex]\[ 4 + 3 = 7 \][/tex]
So,
[tex]\[ 4 - (-3) = 7 \][/tex]
#### Problem 19:
[tex]\[ -7 - (-2) \][/tex]
Rewrite this as:
[tex]\[ -7 + 2 \][/tex]
Calculating this, we get:
[tex]\[ -7 + 2 = -5 \][/tex]
So,
[tex]\[ -7 - (-2) = -5 \][/tex]
#### Problem 20:
[tex]\[ -9 - 1 \][/tex]
Rewrite this as:
[tex]\[ -9 + (-1) \][/tex]
Calculating this, we get:
[tex]\[ -9 + (-1) = -10 \][/tex]
So,
[tex]\[ -9 - 1 = -10 \][/tex]
#### Problem 21:
[tex]\[ 0 - (-9) \][/tex]
Rewrite this as:
[tex]\[ 0 + 9 \][/tex]
Calculating this, we get:
[tex]\[ 0 + 9 = 9 \][/tex]
So,
[tex]\[ 0 - (-9) = 9 \][/tex]
Summarizing all our results:
1. [tex]\( 14 - 6 = 8 \)[/tex]
2. [tex]\( 2 - (-3) = 5 \)[/tex]
3. [tex]\( -3 - 2 = -5 \)[/tex]
4. [tex]\( -4 - (-5) = 1 \)[/tex]
5. [tex]\( 2 - 5 = -3 \)[/tex]
6. [tex]\( 3 - (-3) = 6 \)[/tex]
7. [tex]\( 4 - (-3) = 7 \)[/tex]
8. [tex]\( -7 - (-2) = -5 \)[/tex]
9. [tex]\( -9 - 1 = -10 \)[/tex]
10. [tex]\( 0 - (-9) = 9 \)[/tex]
These are your solutions!
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.